An integrated model of customer loyalty in the Macedonian mobile service market - Palamidovska sterjadovska, Nikolina; Ciunova shuleska, Anita (My University, 2017)
The main objective of this paper is to develop and test an integrated model of customer loyalty in the Macedonian mobile service market, analysing its determinants and their interrelationships and effects on customer loyalty. The proposed research model integrates service quality, customer satisfaction, switching costs and switching barriers as the main determinants of customer loyalty, further analysing their different effects (direct/mediating/moderating) on customer loyalty. Confirmatory factor analysis (CFA) is used in order to assess the validity of the measurement model, and the developed structural model is tested with structural equation modelling (SEM). The reported results indicate that the proposed research model as a whole has a satisfactory level of adequacy and most of the hypothesized realtionships are confirmed. The results suggest that customer satisfaction partially mediates the relationship between service quality and customer loyalty and also service quality has a direct and positive effect on customer loyalty. The satisfaction-loyalty relationship is not mediated nor moderated by switching barriers, but switching barriers have a direct and positive effect on customer loyalty. The presented results would be of great importance for managers for the successful development of strategies for creating mobile service users’ loyalty. The empirical evidence obtained in this study suggest that Macedonian mobile operators should have in mind alternative strategies in creating customer loyalty, emphasising the fact that customer satisfaction has a stronger positive influence in creating customer loyalty than switching barriers. The present research provides an integrated approach in examining customer loyalty and explores the different roles of switching barriers in the relationship between customer satisfaction and loyalty. In order to further develop the integrated approach of customer loyalty modelling, some additional concepts should be incorporated and examined in the future